2017
DOI: 10.1007/s10103-017-2153-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photobiomodulation potentiality by 635 and 809 nm lasers on human osteoblasts

Abstract: Photobiomodulation (PBM) describes light-induced photochemical reactions achieved by the application of red or near infrared lasers/LED light with low energy densities. This noninvasive and painless method has been used in some clinical areas but controversial outcomes demand a skeptical look for its promising and potential effects. In this detailed in vitro study, the osteoblast cells were irradiated with 635 and 809 nm diode lasers at energy densities of 0.5, 1, and 2 J/cm. Cell viability, proliferation, bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
5
14
0
Order By: Relevance
“…Indeed, we demonstrated that as compared to 405 nm, 635 nm in osteoblasts induced: (i) an increase of the expression of vinculin, one of the mechanosensing adhesion protein by which osteoblasts sense matrix stiffness, recognized as a critical regulator of different osteoblast processes including growth, migration, differentiation as well as phenotype maintenance [ 37 , 38 ]; and (ii) an upregulation of all tested osteogenic differentiation markers, namely Runx-2, ALP, OPN as well as an increase of mineralized bone-like nodule structure formation. Our results agree with a recent report showing that PBM with 635 nm did not affect viability and proliferation of CRL-11372 osteoblast-like cells [ 30 ]. In contrast with our findings, that study showed no significant stimulatory effects of this PBM treatment on osteoblast differentiation; this may be dependent on the different responsiveness of the two osteoblast-like cell types to red light or on the different laser parameters used, such as the higher energy doses (0.5, 1, 2 J/cm 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, we demonstrated that as compared to 405 nm, 635 nm in osteoblasts induced: (i) an increase of the expression of vinculin, one of the mechanosensing adhesion protein by which osteoblasts sense matrix stiffness, recognized as a critical regulator of different osteoblast processes including growth, migration, differentiation as well as phenotype maintenance [ 37 , 38 ]; and (ii) an upregulation of all tested osteogenic differentiation markers, namely Runx-2, ALP, OPN as well as an increase of mineralized bone-like nodule structure formation. Our results agree with a recent report showing that PBM with 635 nm did not affect viability and proliferation of CRL-11372 osteoblast-like cells [ 30 ]. In contrast with our findings, that study showed no significant stimulatory effects of this PBM treatment on osteoblast differentiation; this may be dependent on the different responsiveness of the two osteoblast-like cell types to red light or on the different laser parameters used, such as the higher energy doses (0.5, 1, 2 J/cm 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, in our experimental model, 808 nm did not up-regulated, in osteoblasts, neither the expression of OPN nor ALP, which is in agreement with the research by Emes et al [ 78 ] on rat calvarial osteoblast-like cells, by Bölükbaşı Ateş et al [ 30 ] on human CRL-11372 osteoblast like-cells and by Pagin et al [ 79 ] on pre-osteoblasts MC3TR; moreover, such treatment, in hMSCs, reduced the expression of Runx-2 and did not augment that of ALP in accordance to Bouvet-Gerbettaz et al [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, light with improved optical instruments has become a revolutionary breakthrough in the eld of medicine and biomedical sciences [3]. Among various application areas, light can be used to destroy pathogens or cancer cells [4][5][6] and also promote cell proliferation and differentiation [7,8]. Photobiomodulation is speci cally used to stimulate or inhibit cellular processes by changing cellular biochemical activities with the absorption of photon energy by certain cellular components at non-thermal and low-level irradiances [9].…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation (PBM) has demonstrated to be a potentially effective modality in accelerating the healing process and enhancing bone formation (14)(15)(16)(17)(18). Given the successful application of non-ablative lasers to boost formation of new bone, this promising treatment modality was employed by researchers to accelerate healing of peri-implant bone in attempt to shorten the healing time before definitive prosthesis insertion.…”
Section: Introductionmentioning
confidence: 99%